2008
DOI: 10.1002/ejic.200701255
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ketones with Hydrocarbon‐Soluble Calcium Hydride: Stoichiometric Reactions and Catalytic Hydrosilylation

Abstract: Reactions of the dimeric calcium hydride complex[(DIPP‐nacnac)CaH·thf]2 {1; DIPP‐nacnac = CH[(CMe)(2,6‐iPr2C6H3N)]2} with the α‐hydrogen containing ketones acetophenone, acetone, dibenzylketone and 2‐adamantone are smooth. In most cases not only addition but also substantial enolization is observed as a side reaction and in some cases also aldol condensation was found. Despite this unselectivity, the addition products could be isolated crystalline pure. Crystal structures of [(DIPP‐nacnac)CaOCH(Me)Ph]2 (3), [(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 36 publications
1
66
0
2
Order By: Relevance
“…We were also interested in the stoichiometric reactivity of non‐enolisable ketones with 5 . Previously, Group 2 metal‐hydride complexes have been reported to undergo reductions of ketones,,,,, including older reports of less well‐defined MgH species. The reaction of four equivalents of 2‐adamantanone (2‐AdO) with 5 mainly yielded the hydromagnesiated complex 14 [(L 2 Mg 2 (2‐AdOH) 2 (2‐AdO)] (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were also interested in the stoichiometric reactivity of non‐enolisable ketones with 5 . Previously, Group 2 metal‐hydride complexes have been reported to undergo reductions of ketones,,,,, including older reports of less well‐defined MgH species. The reaction of four equivalents of 2‐adamantanone (2‐AdO) with 5 mainly yielded the hydromagnesiated complex 14 [(L 2 Mg 2 (2‐AdOH) 2 (2‐AdO)] (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we attempted the hydrosilylation of our previous two substrates with PhSiH 3 in varying stoichiometries in the presence of catalytic amounts of 5 . Initial studies revealed that treatment of benzophenone with phenylsilane in C 6 D 6 at 70 °C with 1.5 mol % of compound 5 produces the dialkoxysilane, Ph(H)Si(OCHPh 2 ) 2 , as the major product, which was also observed for hydrosilylations of ketones using a calcium‐hydride catalyst . The silane/ketone ratio was therefore chosen to be approximately 1:2 for all further reactions (Table , entries 7–10).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from inter-and intramolecular NH···HB interactions, the amidoborane anion NH 2 BH 3 À was also involved in an agostic BH···Ca 2+ interaction. Thermal decomposition of a solution of Ca(DIPPnacnac)- [11] Solvent-free dimers were only observed with larger bridging groups (X = C CPh, [18] NHBn, [19] OCHPh 2 , [20] OSiMe 3 [21] ). The fact that this complex is free of donors demonstrates the relatively weak coordinating ability of the NH 3 ligand.…”
Section: Thermal Decomposition Of Ca(dippmentioning
confidence: 99%
“…Due to the fact that solid CaH 2 exhibits a very low reactivity numerous attempts were undertaken to prepare soluble calcium derivatives containing a reactive Ca-H bond. Harder and co-workers demonstrated that R-Ca-H is a valuable synthon [5] for the hydrogenation of alkenes [6], an intermediate during hydrosilylation of ketones [7], and reacts also as a strong reducing reagent [8]. Phenylcalcium hydride (R = Ph) was prepared via a cocondensation reaction of calcium with benzene yielding extremely reactive PhCaH [9,10].…”
mentioning
confidence: 99%